Layer-resolved magnetic proximity effect in van der Waals heterostructures - Zhong, Ding; Seyler, Kyle L.; Linpeng, Xiayu; Wilson, Nathan P.; Taniguchi, Takashi; Watanabe, Kenji; McGuire, Michael A.; Fu, Kai-Mei C.; Xiao, Di; Yao, Wang; Xu, Xiaodong (Nature nanotechnology, 2020)
Magnetic proximity effects are integral to manipulating spintronic 1 , 2 , superconducting 3 , 4 , excitonic 5 and topological phenomena 6 – 8 in heterostructures. These effects are highly sensitive to the interfacial electronic properties, such as electron wavefunction overlap and band alignment. The recent emergence of magnetic two-dimensional materials opens new possibilities for exploring proximity effects in van der Waals heterostructures 9 – 12 . In particular, atomically thin CrI 3 exhibits layered antiferromagnetism, in which adjacent ferromagnetic monolayers are antiferromagnetically coupled 9 . Here we report a layer-resolved magnetic proximity effect in heterostructures formed by monolayer WSe 2 and bi/trilayer CrI 3 . By controlling the individual layer magnetization in CrI 3 with a magnetic field, we show that the spin-dependent charge transfer between WSe 2 and CrI 3 is dominated by the interfacial CrI 3 layer, while the proximity exchange field is highly sensitive to the layered magnetic structure as a whole. In combination with reflective magnetic circular dichroism measurements, these properties allow the use of monolayer WSe 2 as a spatially sensitive magnetic sensor to map out layered antiferromagnetic domain structures at zero magnetic field as well as antiferromagnetic/ferromagnetic domains at finite magnetic fields. Our work reveals a way to control proximity effects and probe interfacial magnetic order via van der Waals engineering 13 . Controlling the individual layer magnetization in CrI 3 enables the observation of a layer-resolved magnetic proximity effect in WSe 2 /CrI 3 heterostructures.